OP0062 Osteoporotic hip fractures in men: a rising concern. (12th June 2018) - Sehgal, M.; Mithal, A.; Mithal, A.; Singh, G.
Abstract : Background: Osteoporosis screening and treatment is often exclusively targeted at post-menopausal women. The US Preventive Task Force guidelines recommend bone density screening in women starting at age 65, but do not make any similar recommendation for men, even though men have higher mortality than women after a hip fracture. 1 Recent improvements in health care has led to increasing lifespan of men in US. As more men enter the seventh and eighth decades of their life, they are at more risk for developing osteoporosis and osteoporotic hip fractures. Objectives: To study the number and prevalence of hospitalizations for osteoporotic hip fractures in the men and women aged 50 years and up in the US over 23 years (1993–2015). Methods: The National Inpatient Sample (NIS) is a stratified random sample of all US community hospitals and is the only US national hospital database with information on all patients, regardless of payer, including persons covered by Medicare, Medicaid, private insurance, and the uninsured. We examined all inpatient hospitalizations in NIS from 1993 to 2015 with a primary diagnosis of non-traumatic (osteoporotic) hip fractures in individuals 50 years and older. Patients were excluded if there was any evidence of major trauma, open fractures, or primary or secondary femoral tumours. US population estimates and projections for the resident US population were obtained from the US Census Bureau. All prevalence rates were expressed per 1 00 000 of the US population. Results: From 1993 to 2015, we studied 6.3 million osteoporotic hip fracture hospitalizations in 1.99 billion person-years of observation in individuals who were 50 years or older. Of these, 74% occurred in women. Hip fracture hospitalizations in women decreased from 2 09 052 in 1993 (prevalence 562 per 1 00 000 person-years) to 2 01 435 in 2015 (340 per 1 00 000 person-years), even as the population of 50 years and older women increased from 37 million in 1993 to 59 million in 2015 (59% increase in population), perhaps reflecting increasing awareness, screening and treatment for osteoporosis in elderly women. However, in men aged 50 years and older, osteoporotic hip fracture hospitalizations increased from 64 339 in 1993 to 83 885 in 2015, even as the prevalence decreased from 218 per 1 00 000 person-years in 1993 to 162 per 1 00 000 person-years in 2015. The 30% increase in the absolute number of hip fracture hospitalizations, despite decreasing prevalence, is coincident with the 75% rise in the number of the 50 years and older men population, from 29.6 million in 1993 to 51.7 million in 2015. Conclusions: Despite an overall decrease in prevalence, the absolute number of osteoporotic hip fracture hospitalizations increased in 50 years and older men. More attention needs to be paid to prevention of osteoporotic hip fractures in this cohort. Reference: [1] Hawkes WG, et al. Gender differences in functioning after hip fracture. J Gerontol A Biol Sci Med Sci2006;61(5):495–9. Disclosure of Interest: None declared